Ferroic superglasses: Relaxor ferroelectrics PMN and SBN vs. CoFe superspin glass. (3rd October 2018) - Kleemann, Wolfgang; Dec, Jan
Abstract: Random electric fields (RF) due to charge disorder are at the origin of polar nanoregions (PNR) in the cubic relaxor PbMg1/3 Nb2/3 O3 . They initiate Lacroix-Béné-type Cole-Cole semicircles, which achieve Cole-Davidson skew and dynamic power law criticality upon approaching superdipolar glass freezing. Below T g ≈ 240 K percolation of PNR into microdomains is evidenced by interfacial creep and relaxation via Cole-Cole diagrams. Similar behavior occurs in uniaxial Sr0.8 Ba0.2 Nb2 O6 ( T g ≈ 301 K). In contrast, matrix isolated ferromagnetic nanoparticles in CoFe/Al2 O3 multilayers without RF interaction lack all of these effects except superglassy critical dynamics at T g ≈ 46 K.